Hydrogenation catalyst, process for its preparation and use
Patent Information
- Application Number
- CN202510455688.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-04-11
- Publication Date
- 2026-10-20
AI Technical Summary
[0004]本发明的目的是为了克服现有技术存在的加氢催化剂深度加氢活性有待进一步提高的问题,提供一种加氢催化剂及其制备方法与应用,该催化剂具有良好的芳烃加氢饱和活性
[0013]本发明的发明人在研究过程中发现具有适宜的孔分布且高孔集中度的载体能够为渣油中的稠环芳烃分子提供更好的活性相的可接近性以及更高的反应效率;与此同时,进一步改善活性相和表面性质,能够减弱催化剂表面对于胶质、沥青质等稠环芳烃类化合物的吸附引起的积炭,增加催化剂的稠环芳烃饱和活性和稳定性;进一步地,通过引入碳元素,可起到隔离活性相长大,从而有利于活性相边角位比例的提高,进而提高催化剂的活性和稳定性。
Smart Images

Figure SMS_5 
Figure SMS_6 
Figure SMS_7
Abstract
Description
Technical Field
[0001] This invention relates to the technical field of hydrogenation catalysts, specifically to hydrogenation catalysts, their preparation methods, and applications. Background Technology
[0002] The replacement of gasoline-powered vehicles with new energy vehicles is accelerating, leading to a slowdown in the growth rate of refined oil end-user consumption; however, demand for light petroleum oil for chemical production is increasing significantly. At the same time, the trend of crude oil becoming heavier and of lower quality is intensifying. To transform these inferior feedstocks into high-value chemicals and chemical feedstocks, heavy oil conversion technologies such as hydrocracking and catalytic cracking are required.
[0003] Heavy oil hydrotreating-catalytic cracking combined feedstock enhancement technology can provide higher propylene yields. By modifying reaction conditions, it can selectively produce ethylene and aromatics, offering superior product structure flexibility. Existing research shows that the higher the hydrogen content of the DCC feedstock (i.e., hydrotreated heavy oil), the higher the content of alkanes and cycloalkanes, and the higher the propylene yield of the DCC unit. However, polycyclic aromatic hydrocarbons (PAHs) inevitably undergo coking reactions during the DCC process. Achieving efficient conversion of PAHs in the heavy oil hydrotreating unit is the best way to change the reaction pathway of PAHs in the DCC process, and it is also the core challenge of this technology. How to convert polycyclic aromatic hydrocarbons, gums, and asphaltenes in heavy oil into easily catalytically crackable alkanes, cycloalkanes (monocyclic to tetracyclic cycloalkanes), and monocyclic aromatic hydrocarbons through deep hydrotreating is a highly valuable research direction. Summary of the Invention
[0004] The purpose of this invention is to overcome the problem that the deep hydrogenation activity of existing hydrogenation catalysts needs to be further improved, and to provide a hydrogenation catalyst, its preparation method and application, which has good aromatic hydrogenation saturation activity.
[0005] To achieve the above objectives, a first aspect of the present invention provides a hydrogenation catalyst, wherein the catalyst comprises an alumina support, a hydrogenation active metal component, and carbon, the hydrogenation active metal component comprising Group VIII and Group VIB metal elements; the pore concentration A of the alumina support is 0.8-3, and the pore volume of the 4-13 nm pores of the alumina support accounts for 78-95% of the total pore volume; the carbon content is 0.1-5% based on the total weight of the catalyst.
[0006] A second aspect of the present invention provides a method for preparing a hydrogenation catalyst, wherein the method includes the following steps:
[0007] (1) Neutralize aluminum sulfate solution with alkaline solution to obtain neutralized slurry. The pH of the neutralization reaction is 8-10.
[0008] (2) The neutralized slurry is subjected to a first aging process to obtain a first aged solid product. The pH of the first aging process is higher than that of the neutralization reaction.
[0009] (3) In the presence of a solvent, the first aged solid product is subjected to a second aging to obtain a second aged solid product. Then, the second aged solid product is subjected to a first drying to obtain boehmite. The pH of the first aging is higher than that of the second aging.
[0010] (4) The pseudoboehmite is optionally shaped, and then subjected to a second drying and a first calcination to obtain an alumina carrier;
[0011] (5) A carbon source and a hydrogenated active metal component are introduced into the alumina support, followed by a third drying and a second calcination. The hydrogenated active metal component includes Group VIII and Group VIB metal elements. The amount of carbon source is such that the carbon content in the prepared catalyst is 0.1-5% based on the total weight of the catalyst.
[0012] The third aspect of this invention provides the application of the catalyst described in the first aspect or the catalyst prepared by the method described in the second aspect in the hydrotreating of hydrocarbon oils.
[0013] During their research, the inventors of this invention discovered that a support with a suitable pore distribution and high pore concentration can provide better accessibility of the active phase and higher reaction efficiency for polycyclic aromatic hydrocarbon molecules in residual oil. Simultaneously, further improvements to the active phase and surface properties can reduce coking caused by the adsorption of polycyclic aromatic hydrocarbons such as gums and asphaltenes on the catalyst surface, increasing the catalyst's polycyclic aromatic hydrocarbon saturation activity and stability. Furthermore, by introducing carbon elements, the growth of the active phase can be isolated, thereby improving the proportion of active phase edge and corner sites, and further enhancing the catalyst's activity and stability.
[0014] The method provided by this invention uses aluminum sulfate solution as raw material to prepare pseudoboehmite by combining a neutralization reaction with two aging reactions. During the preparation process, the pH value of each reaction is precisely controlled. The neutralization reaction is carried out under alkaline conditions, resulting in a larger number of primary pseudoboehmite crystals that are easier to grow into uniform crystals. Furthermore, by controlling the pH of the first aging process to be higher than that of the neutralization reaction, the pseudoboehmite crystals can grow rapidly and uniformly during the first aging process. Even further, controlling the pH of the first aging process to be higher than that of the second aging process is beneficial for the removal of impurity ions and, in conjunction with other conditions in each reaction stage, yields pseudoboehmite with relatively high crystallinity, concentrated pore distribution, and low impurity content. Furthermore, alumina prepared from the aforementioned pseudoboehmite is used as the catalyst support, and the surface properties of the support are controlled by calcination conditions to obtain a specific content of alumina hydroxyl, which can reduce coking on the catalyst surface and improve the catalyst's reactivity. Even further, by introducing carbon, the growth of the active phase can be isolated, thereby improving the proportion of active phase edge and corner sites.
[0015] The catalyst provided by this invention has good saturated activity and reaction stability in aromatic hydrogenation. Using the catalyst of this invention for the hydrogenation reaction of residue oil can improve the reaction activity. Detailed Implementation
[0016] The endpoints and any values of the ranges disclosed herein are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of the various ranges, the endpoint values of the various ranges and individual point values, and individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed herein.
[0017] The first aspect of this invention provides a hydrogenation catalyst, wherein the catalyst comprises an alumina support, a hydrogenation active metal component, and carbon, the hydrogenation active metal component comprising Group VIII and Group VIB metal elements; the pore concentration A of the alumina support is 0.8-3, and the pore volume of the 4-13 nm pores of the alumina support accounts for 78-95% of the total pore volume; the carbon content is 0.1-5% based on the total weight of the catalyst.
[0018] During the research process, the inventors of this invention discovered that a support with a suitable pore distribution and high pore concentration can provide better accessibility of the active phase and higher reaction efficiency for polycyclic aromatic hydrocarbon molecules in residual oil. Further improvements in the active phase and surface properties can reduce coking caused by the adsorption of polycyclic aromatic hydrocarbons such as gums and asphaltenes on the catalyst surface, thereby increasing the saturated activity and stability of the catalyst for polycyclic aromatic hydrocarbons. Furthermore, by introducing carbon elements, the growth of the active phase can be isolated, which is beneficial to increasing the proportion of active phase edge and corner sites.
[0019] In this invention, the pore concentration A of the alumina carrier refers to the highest DV value (DV) in the BET pore size distribution diagram-DV curve. MAX The ratio of the peak width at half maximum (FWHM) to the peak width at half maximum (FWHM), i.e., A = DV. MAX / FWHM. An SAP2420 automated adsorption analyzer (Micromerities Instruments, USA) was used to determine the specific surface area and pore structure of the carrier using the N2 static low-temperature adsorption capacity method. Before testing, the sample was degassed under vacuum at 300℃ and 1.33 Pa for 10 hours, then contacted with the N2 adsorbate at 196℃ to reach static adsorption equilibrium. The amount of N2 adsorbed by the sample was calculated from the difference between the N2 inlet gas rate and the amount remaining in the gas phase after adsorption. The surface area was calculated using the BET formula.
[0020] In this invention, the carbon content in the catalyst is determined by infrared absorption. The specific testing method is as follows: the sample and the co-solvent are placed in a high-frequency induction furnace, oxygen is introduced for combustion, and the generated CO2 gas flows through the infrared absorption cell to absorb infrared energy. The C content can be obtained from the change in energy.
[0021] In this invention, preferably, the pore concentration A of the alumina support is 1.9-2.5. By selecting alumina with a high pore concentration as the support, the reaction activity of the catalyst can be further improved.
[0022] In this invention, preferably, the pore volume of the alumina support with 4-13 nm pores accounts for 85-90% of the total pore volume. By selecting alumina with a higher effective pore ratio as the support, the reaction activity of the catalyst can be further improved.
[0023] In this invention, preferably, the carbon content is 0.3-2% based on the total weight of the catalyst.
[0024] In this invention, preferably, the pore volume of the alumina support is 0.58-0.75 mL / g.
[0025] In this invention, preferably, the specific surface area of the alumina carrier is 250-310 m². 2 / g.
[0026] In this invention, preferably, the alumina carrier has a pore diameter of 5-9 nm.
[0027] In this invention, preferably, based on the dry weight of the alumina support and in terms of oxides, the sodium content is 0.01-0.05%, more preferably 0.012-0.03%, and the S content is 0.1-1%, more preferably 0.2-0.8%. Using alumina with a lower impurity content as a support can improve the quality of the catalyst.
[0028] In this invention, the contents of S and Na in the alumina support were determined by XRF characterization. XRF characterization was performed using a Rigaku Electric Industries, Ltd. (RIGE) 3271 X-ray fluorescence spectrometer. A scintillation counter and a proportional counter were used to detect the intensity of elemental spectral lines, and the external standard method was used for quantitative analysis of the elemental contents. The powder sample was pressed into tablets using a rhodium target, with a laser voltage of 50 kV and a laser current of 50 mA.
[0029] In this invention, preferably, based on the total weight of the catalyst, the content of the alumina support is 30-99%, the content of the Group VIII metal element (calculated as oxide) is 0.5-20%, and the content of the Group VIB metal element (calculated as oxide) is 0.5-50%; preferably, based on the total weight of the catalyst, the content of the alumina support is 40-94%, the content of the Group VIII metal element (calculated as oxide) is 1-15%, and the content of the Group VIB metal element (calculated as oxide) is 5-45%.
[0030] In this invention, the content of each component in the catalyst is determined by fluorescence method.
[0031] In this invention, preferably, the Group VIII metal element is cobalt and / or nickel.
[0032] In this invention, preferably, the Group VIB metal element is molybdenum and / or tungsten.
[0033] The hydrogenation catalyst provided by the present invention may also contain any additives that do not affect the performance of the hydrogenation catalyst of the present invention or can improve the performance of the hydrogenation catalyst of the present invention, such as at least one of the elements of group IA, IIA, IIIA, IVA, VA, VIIA, IIB, IIIB and rare earth metal elements, preferably at least one of phosphorus, boron, fluorine, silicon, sodium, magnesium, lithium, zinc, calcium, potassium, lanthanum and cerium.
[0034] In this invention, preferably, based on the total weight of the catalyst and in terms of elements, the content of the auxiliary agent does not exceed 10%, and is more preferably 0.5-6%.
[0035] In this invention, preferably, the TEM active phase length of the catalyst is 1.8-5 nm, more preferably 2.1-3.2 nm. The advantage of this preferred embodiment is that the shorter the active phase size, the higher the proportion of corner sites, which is beneficial for improving desulfurization and hydrogenation saturation activity.
[0036] In this invention, the TEM active phase of the catalyst was measured using an instrument from FEI Corporation, specifically a FEI TECNAI G. 2 The F20S-TWIN transmission electron microscope is equipped with a scanning transmission attachment and an X-ray energy dispersive spectroscopy (EDS) attachment (EDS attachment is an EDAX product). To avoid oxidation of the sulfided catalyst during sample preparation, the sulfided sample needs to be ground in a mortar containing liquid cyclohexane. The powdered sample and cyclohexane are then sealed together in a small sample vial. Suspension preparation and microgrid preparation microscopy are used for sample observation. All catalysts are observed under the same TEM conditions, using the same magnification and accelerating voltage. 20-30 images are taken for each sample to ensure a statistical area greater than 30,000 nm. 2 Computer software was used to statistically analyze the length, number of layers, and number of fringes. The statistical average length of the MoS2 wafer was determined. The statistical average number of stacking layers is obtained from Formula 2.1. Calculated according to formula 2.2, 1000nm 2 Average number of MoS2 lamellar crystals per observed area It is calculated using formula 2.3.
[0037] Average grain length (Unit: nm)
[0038]
[0039] Among them, l i Let be the length of the fringe image of the i-th MoS2 lamella, and n be the total number of grains in the statistical region.
[0040] A second aspect of the present invention provides a method for preparing a hydrogenation catalyst, wherein the method includes the following steps:
[0041] (1) Neutralize aluminum sulfate solution with alkaline solution to obtain neutralized slurry. The pH of the neutralization reaction is 8-10.
[0042] (2) The neutralized slurry is subjected to a first aging process to obtain a first aged solid product. The pH of the first aging process is higher than that of the neutralization reaction.
[0043] (3) In the presence of a solvent, the first aged solid product is subjected to a second aging to obtain a second aged solid product. Then, the second aged solid product is subjected to a first drying to obtain boehmite. The pH of the first aging is higher than that of the second aging.
[0044] (4) The pseudoboehmite is optionally shaped, and then subjected to a second drying and a first calcination to obtain an alumina carrier;
[0045] (5) A carbon source and a hydrogenation active metal component are introduced into the alumina support, followed by a third drying and a second calcination. The second calcination is carried out under nitrogen and / or an inert atmosphere. The hydrogenation active metal component includes Group VIII metal elements and Group VIB metal elements. The amount of carbon source is such that the carbon content in the prepared catalyst is 0.1-5% based on the total weight of the catalyst.
[0046] The method provided by this invention uses aluminum sulfate solution as raw material and combines a neutralization reaction with two aging reactions to prepare boehmite. During the preparation process, the pH value of each reaction is precisely controlled. The neutralization reaction is carried out under alkaline conditions, resulting in a larger number of primary boehmite crystals that are easier to grow into uniform crystals. Furthermore, by controlling the pH of the first aging process to be higher than that of the neutralization reaction, the boehmite crystals can grow rapidly and uniformly during the first aging process. Even further, controlling the pH of the first aging process to be higher than that of the second aging process is beneficial for the removal of impurity ions and synergistically enhances the effects of other conditions in each reaction stage. This process yields boehmite with relatively high crystallinity, concentrated pore distribution, and low impurity content. Furthermore, alumina prepared from the aforementioned boehmite is used as the catalyst support, and the surface properties of the support are controlled by synergistic calcination conditions to obtain alumina with a specific content of hydroxyl groups. This reduces coking on the catalyst surface and improves the catalyst's reactivity. Moreover, altering the main and edge structures of the active phase weakens the catalyst's saturation performance for tetracyclic or higher aromatic hydrocarbons, increasing the catalyst's desulfurization selectivity. Even further, introducing carbon elements isolates the growth of the active phase, which is more conducive to the formation of small-sized active phases during sulfidation.
[0047] In this invention, preferably, the pH of the first aging process is 0.05-2.2 higher than the pH of the neutralization reaction, more preferably 0.1-2 higher. The advantage of this preferred embodiment is that the boehmite grains can grow more rapidly and uniformly during the first aging process, which is beneficial for forming a boehmite product with uniform grain size.
[0048] In this invention, preferably, the pH of the first aging process is 0.5-1.8 higher than the pH of the second aging process, and more preferably 0.7-1.5 higher. The advantage of this preferred embodiment is that it facilitates the removal of impurity ions in the subsequent washing process, resulting in boehmite with low impurity content.
[0049] In this invention, by controlling the concentration of the raw material aluminum sulfate solution, increasing the second aging and washing to reduce impurities, pseudoboehmite with low impurity content is obtained, thereby improving the quality of pseudoboehmite. Preferably, in step (1), the concentration of the aluminum sulfate solution, based on alumina, is 40-100 g / L, more preferably 50-90 g / L.
[0050] In this invention, there is no particular limitation on the type of alkaline solution; any alkaline solution conventionally defined in the art can be applied to this invention. Preferably, in step (1), the alkaline solution is selected from at least one of sodium hydroxide solution, sodium carbonate solution, and sodium aluminate solution, and is preferably sodium aluminate solution.
[0051] In this invention, the concentration of the alkaline solution is not particularly limited, as long as it meets the pH requirements for the neutralization reaction. Preferably, the concentration of the alkaline solution is 100-250 g / L, and more preferably 150-240 g / L.
[0052] In this invention, preferably, the volume ratio of the aluminum sulfate solution to the alkaline solution is 3-4:1, and more preferably 3.6-3.9:1.
[0053] In this invention, there is no particular limitation on the method of neutralization reaction. In step (1), the neutralization reaction is carried out continuously or intermittently, preferably continuously. Carrying the neutralization reaction continuously is more conducive to controlling the pH of the neutralization reaction process, thereby improving the quality of boehmite. On the other hand, continuous operation can increase the throughput per unit time and improve production efficiency.
[0054] In this invention, the range of conditions for the neutralization reaction is relatively wide. Preferably, in step (1), the conditions for the neutralization reaction include: a temperature of 45-75°C and a residence time of 5-30 min.
[0055] In this invention, by further controlling the pH of the neutralization reaction, the neutralization reaction is carried out under alkaline conditions. This results in a larger number of pseudoboehmite primary grains being directly generated during the neutralization reaction, which are easier to grow into uniform grains. Preferably, in step (1), the pH of the neutralization reaction is 8.2-9.5.
[0056] The present invention does not particularly limit the equipment used for the neutralization reaction; for example, it can be carried out in a reaction vessel.
[0057] In this invention, the selection range of the conditions for the first aging is relatively wide. Preferably, in step (2), the conditions for the first aging include: a temperature of 75-99°C and a time of 2-30h; more preferably, in step (2), the conditions for the first aging include: a temperature of 81-98°C and a time of 4-26h.
[0058] In this invention, by increasing the pH of the first aging process and strictly controlling the pH of the first aging process, the crystals of boehmite can grow rapidly and uniformly during the first aging process. Preferably, in step (2), the pH of the first aging process is 9-10.8, and more preferably 9.5-10.6.
[0059] In this invention, preferably, step (2) further includes: optionally adding an aluminum-free alkaline compound solution to the neutralized slurry to adjust the pH to 9-10.8, preferably to 9.5-10.6, for a first aging.
[0060] In this invention, the type of aluminum-free alkaline compound solution is not particularly limited. Preferably, the aluminum-free alkaline compound solution is selected from at least one of sodium hydroxide solution, sodium carbonate solution, sodium bicarbonate solution, and ammonia water, and more preferably sodium carbonate solution.
[0061] In this invention, there are no particular limitations on the concentration and amount of the aluminum-free alkaline compound solution, as long as it can meet the pH required for the first aging. Those skilled in the art can adjust it according to actual needs.
[0062] In this invention, preferably, step (2) further includes: subjecting the neutralized slurry to a first aging process to obtain a first aged slurry, and then performing solid-liquid separation and washing on the first aged slurry to obtain a first aged solid product. This invention does not particularly limit the method of solid-liquid separation; any method conventionally defined in the art that can achieve solid-liquid separation is applicable to this invention, such as conventional filtration and washing methods like vacuum filtration and plate-and-frame filtration. This invention also does not particularly limit the washing conditions; for example, washing can be performed with a detergent at 75-95°C, resulting in a Na2O content of less than 0.5% in the boehmite filter cake after washing. This invention also does not particularly limit the type of detergent; for example, water can be used.
[0063] In this invention, preferably, step (3) further includes: mixing the first aged solid product and a solvent to form a slurry, thereby obtaining a slurry containing the first aged solid product. The advantage of this preferred embodiment is that the solid product particles are uniformly dispersed in the solution, which facilitates the complete dissolution of impurity ions into the solvent.
[0064] In this invention, the type of solvent is not particularly limited; for example, it can be water and / or alcohol, with water being preferred.
[0065] In this invention, the specific operation method of pulping is not particularly limited, as long as the pulping of the first aged solid product is achieved, for example, it can be mixed pulping.
[0066] In this invention, the conditions for slurry preparation are not particularly limited, as long as the concentration of the slurry containing the first aged solid product is sufficient. Preferably, in step (3), the concentration of the slurry containing the first aged solid product, calculated as alumina, is 40-150 g / L, more preferably 45-70 g / L. The advantage of this preferred embodiment is the uniform dispersion of the solid product particles in the solution, which facilitates the complete dissolution of impurity ions into the solvent.
[0067] In this invention, the conditions for the second aging are not particularly limited. Preferably, in step (3), the conditions for the second aging include: a temperature of 55-90°C and a time of 2-6 hours; more preferably, in step (3), the conditions for the second aging include: a temperature of 60-88°C and a time of 3-5 hours.
[0068] In this invention, preferably, in step (3), the pH of the second aging process is 8.5-10.5, more preferably 8.7-9.8. The advantage of this preferred embodiment is that it facilitates the removal of impurity ions in the subsequent washing process, resulting in boehmite with low impurity content.
[0069] In this invention, preferably, step (3) further includes: optionally adding an aluminum-free alkaline compound solution to the slurry containing the first aged solid product to adjust the pH to 8.5-10.5, preferably to 8.7-9.8, for a second aging.
[0070] In this invention, there is no particular limitation on the type of aluminum-free alkaline compound solution. It can be the same as or different from the type of aluminum-free alkaline compound solution used in the first aging step (2), but preferably the same.
[0071] In this invention, it is understood that when the Na2O impurity content in the first aged solid product obtained by solid-liquid separation and washing of the first aged slurry is low, and the pH of the slurry of the first aged solid product is lower than the pH required for the second aging, an aluminum-free alkaline compound solution can be added to the slurry containing the first aged solid product to adjust the pH; when the Na2O impurity content in the first aged solid product obtained by solid-liquid separation and washing of the first aged slurry is high, and the pH of the slurry of the first aged solid product is within the pH range required for the second aging, it is not necessary to add an aluminum-free alkaline compound solution to the slurry containing the first aged solid product to adjust the pH.
[0072] In this invention, the method of the first drying in step (3) is not particularly limited; for example, it can be drying in an oven. The conditions for the first drying in step (3) are not particularly limited in this invention; preferably, the drying temperature is 80-150°C.
[0073] In this invention, the molding method of step (4) is not particularly limited. It can adopt the molding method conventionally defined in the art. In a preferred case, the molding includes adding adhesive solvent and additives and extruding and mixing with pseudoboehmite during the mixing molding process in step (4).
[0074] In this invention, the type of extrusion aid is not particularly limited, and any extrusion aid conventionally defined in the art is applicable to this invention. Preferably, the extrusion aid can be guar gum powder or cellulose, which can be selected by those skilled in the art according to conventional methods.
[0075] In this invention, the type of adhesive solvent is not particularly limited, and adhesive solvents conventionally defined in the art are all applicable to this invention. Preferably, the adhesive solvent can be an acid, more preferably a protic acid, and more preferably at least one of nitric acid, acetic acid, and oxalic acid, which can be selected by those skilled in the art according to conventional methods.
[0076] The present invention does not impose any particular limitation on the amount of the adhesive solvent and the extrusion aid, and the amounts can be selected in accordance with conventional methods in the art to ensure smooth subsequent molding.
[0077] In this invention, water may or may not be added during the mixing process described in step (4). This invention does not impose any particular limitation on the amount of water used, as long as the subsequent molding process is successful.
[0078] The present invention does not particularly limit the molding method described in step (4). Commonly used molding methods in the field can be adopted, such as at least one of extrusion molding, spray molding, roll forming and sheet forming, with extrusion molding being preferred.
[0079] In this invention, the method of the second drying in step (4) is not particularly limited. For example, it can be a conventional method in the art, such as oven drying, forced air drying, and mesh belt drying. The conditions for the second drying in step (4) are not particularly limited in this invention. Preferably, the drying temperature is 80-200℃, and more preferably 100-150℃.
[0080] In this invention, the conditions for the first roasting are not particularly limited. Preferably, in step (4), the conditions for the first roasting include: a temperature of 450-800℃ and a time of 1-10h; preferably, in step (4), the conditions for the first roasting include: a temperature of 500-700℃ and a time of 2-6h.
[0081] In this invention, the third drying conditions described in step (5) are the conditions commonly used for preparing such catalysts, such as a drying temperature of 80-350°C, preferably 100-300°C, and a drying time of 1-24 hours, preferably 2-12 hours.
[0082] In this invention, the conditions for the second roasting are not particularly limited. Preferably, in step (5), the conditions for the second roasting include: a temperature of 450-800℃ and a time of 1-10h; preferably, in step (4), the conditions for the second roasting include: a temperature of 500-700℃ and a time of 2-6h.
[0083] The present invention does not particularly limit the method for introducing the active metal, and various methods conventionally used in the art can be employed, such as impregnation and co-precipitation. Preferably, the active metal is introduced onto the alumina support using the impregnation method.
[0084] In this invention, preferably, the method includes: impregnating an alumina support in an impregnation solution containing a compound of a Group VIII metal element and a Group VIB metal element, followed by a third drying and vacuum calcination.
[0085] The present invention does not specifically limit the method of impregnation. The method of impregnation can be impregnation with excess liquid or impregnation with equal volume, depending on the amount of impregnation liquid used.
[0086] The present invention offers a wide range of choices for compounds of the Group VIII metal elements, which can be conventional choices in the art. Preferably, the compounds of the Group VIII metal elements are selected from at least one of the nitrates, acetates, carbonates, chlorides, and soluble complexes of the Group VIII metal elements. Further, taking cobalt as an example, it can be selected from at least one of cobalt nitrate, cobalt acetate, basic cobalt carbonate, and cobalt chloride, preferably cobalt nitrate and / or basic cobalt carbonate. Taking nickel as an example, it can be selected from at least one of nickel-containing salts, oxides, and hydroxides, such as at least one of nickel nitrates, chlorides, formates, acetates, phosphates, citrates, oxalates, carbonates, basic carbonates, hydroxides, phosphides, sulfides, and oxides, preferably at least one of nickel oxalates, carbonates, basic carbonates, hydroxides, phosphates, and oxides, more preferably at least one of nickel nitrate, nickel acetate, basic nickel carbonate, nickel chloride, and nickel carbonate.
[0087] The present invention allows for a wide range of choices of compounds containing the Group VIB metal elements, which can be conventional choices in the art. Preferably, the compounds containing the Group VIB metal elements are selected from at least one of molybdates, tungstates, metatungstates, and ethyl metatungstates. Further, taking molybdenum as an example, salts and / or oxides of molybdenum metal can be selected from at least one of molybdenum oxide, molybdates, paramolybdates, and phosphomolybdates, preferably at least one of molybdenum oxide, ammonium molybdate, ammonium paramolybdate, and phosphomolybdic acid.
[0088] In this invention, preferably, the amounts of Group VIII and Group VIB metal elements used are such that, based on the total weight of the catalyst, the content of the alumina support is 30-99%, the content of the Group VIII metal element (calculated as oxide) is 0.5-20%, and the content of the Group VIB metal element (calculated as oxide) is 0.5-50%; preferably, based on the total weight of the catalyst, the content of the alumina support is 40-94%, the content of the Group VIII metal element (calculated as oxide) is 1-15%, and the content of the Group VIB metal element (calculated as oxide) is 5-45%.
[0089] In this invention, preferably, the Group VIII metal element is cobalt and / or nickel.
[0090] In this invention, preferably, the Group VIB metal element is molybdenum and / or tungsten.
[0091] In this invention, when the catalyst also contains an auxiliary component, the introduction method can be as follows: directly mixing the compound containing the auxiliary element with boehmite, molding, and calcining; preparing a mixed solution of the compound containing the auxiliary element and a compound containing an active metal and then contacting it with the alumina support; or preparing a solution of the compound containing the auxiliary element separately and then contacting it with the alumina support and calcining it. When the auxiliary and active metal are introduced into the alumina support separately, it is preferable to first contact and calcine the alumina support with the compound containing the auxiliary element, and then contact it with a solution of the compound containing the active metal, for example, through ion exchange, impregnation, co-precipitation, or other methods.
[0092] In this invention, preferably, the amount of the auxiliary agent is such that, based on the total weight of the catalyst and in terms of elements, the content of the auxiliary agent in the prepared catalyst does not exceed 10%, preferably 0.5-6%.
[0093] In this invention, preferably, in step (5), the carbon source is selected from at least one of organic acids, organic alcohols and sugar compounds.
[0094] In this invention, preferably, the organic acid is selected from at least one of acetic acid, maleic acid, oxalic acid, aminotriacetic acid, 1,2-cyclohexanediaminetetraacetic acid, citric acid, tartaric acid, and malic acid.
[0095] In this invention, preferably, the organic alcohol is selected from at least one of glycerol, ethylene glycol, glycerol, polyethylene glycol (molecular weight 200-1500), diethylene glycol, butanediol and propanol.
[0096] In this invention, preferably, the carbohydrate compound is selected from at least one of glucose, maltose, lactose and sucrose.
[0097] In this invention, preferably, the amount of carbon source is such that the carbon content in the prepared catalyst is 0.3-2% based on the total weight of the catalyst.
[0098] The third aspect of this invention provides the application of the catalyst described in the first aspect or the catalyst prepared by the method described in the second aspect in the hydrotreating of hydrocarbon oils.
[0099] The apparatus for the hydrotreating reaction described in this invention can be carried out in any reactor capable of bringing the feedstock into contact with the catalyst under hydrotreating reaction conditions, for example, in a fixed-bed reactor, a moving-bed reactor, or a fluidized-bed reactor.
[0100] In this invention, preferably, the catalyst is pre-sulfurized before use. The pre-sulfurization treatment can be performed using conventional methods in the art, for example, the catalyst can be pre-sulfurized in a hydrogen-containing atmosphere and in the presence of a sulfurizing agent. Preferably, the sulfurizing agent is selected from at least one of sulfur, hydrogen sulfide, and sulfur-containing raw materials. Preferably, the pre-sulfurization temperature is 140-400°C.
[0101] In this invention, the pre-sulfurization can be carried out outside the apparatus or in situ inside the apparatus to convert the active metal loaded thereon into metal sulfides.
[0102] The catalyst provided by this invention has good saturated activity for aromatic hydrocarbon hydrogenation. Using the catalyst of this invention for the hydrogenation reaction of residue oil can improve the hydrogenation reaction activity.
[0103] The present invention will be described in detail below through embodiments. Unless otherwise specified, all raw materials used in the following embodiments are commercially available products.
[0104] Example 1
[0105] Preparation of reaction raw materials:
[0106] 1.92 L of industrial aluminum sulfate solution (Zibo Qimao Catalyst Co., Ltd., with a concentration of 104 g / L based on alumina, a free acid concentration of 3 g H2SO4 / L, and a Fe2O3 concentration ≤150 mg / L) and deionized water were mixed to prepare 4 L of aluminum sulfate solution, wherein the concentration of aluminum sulfate solution based on alumina was 50.0 g / L.
[0107] A 6.5 L sodium aluminate solution was prepared by heating and dissolving NaOH (Sinopharm Group), aluminum hydroxide (Guangxi Branch of Aluminum Corporation of China Limited, alumina content 64.0%) and deionized water. The sodium aluminate solution contained Al2O3 concentration of 220 g / L and Na2O concentration of 227 g / L.
[0108] Prepare 2L of Na2CO3 solution with a concentration of 200g / L (from Sinopharm Group).
[0109] The preparation of pseudoboehmite according to the method provided by this invention includes the following specific steps:
[0110] (1) Add the prepared 4L aluminum sulfate solution and 1.2L sodium aluminate solution to two raw material tanks respectively. Use a metering pump to adjust and control the flow rate volume ratio of aluminum sulfate solution to sodium aluminate solution to 3.85. Add them in parallel to a 2.0L neutralization reactor for continuous neutralization reaction at a temperature of 60℃, pH of 8.3 and residence time of 20min. The slurry overflows into the aging reactor.
[0111] (2) Add 1000 mL of Na2CO3 solution to the slurry after neutralization (neutralized slurry), adjust the pH to 10.2, and heat to 85℃ and hold at that temperature for 3 hours for the first aging. Filter the slurry after the first aging (first aged slurry) using a vacuum filter, and wash with 60 L of deionized water at 90℃ to obtain a filter cake (i.e., the first aged solid product) with a Na2O content of 0.4%.
[0112] (3) The filter cake was slurried with deionized water to form 6L of slurry containing the first aging solid product. The concentration of the slurry was 45g / L based on alumina. 20mL of Na2CO3 solution was added to the slurry containing the first aging solid product to adjust the pH of the slurry to 9.5. The slurry was heated to 62℃ and kept at that temperature for 2h for the second aging. The filter cake (the second aging solid product) was dried (drying temperature was 120℃) to obtain pseudoboehmite PB-1.
[0113] XRD characterization revealed that PB-1 possesses a pseudoboehmite structure. The relative crystallinity and grain size of the pseudoboehmite were calculated based on the 2θ = 38° peak in the pseudoboehmite phase diagram, and the results are shown in Table 1. PB-1 was calcined in a crucible at 600℃ for 3 hours to obtain alumina powder A-1. A-1 possesses a γ-alumina phase, and its chemical composition was characterized by XRF, with the results listed in Table 1. The pore volume, specific surface area, and dilatant pore diameter of A-1 were measured using the N2 adsorption method, and the results are shown in Table 1.
[0114] (4) Take 100g of PB-1, add 80g of deionized water, 2.8mL of concentrated nitric acid, and 3.0g of guar gum powder. Mix thoroughly and knead evenly on an extruder to obtain a paste. Extrude the paste into shape on the extruder and dry it in an oven at 120℃ for 4 hours. The dried strips are then calcined at 600℃ in a tubular calcining furnace for 3 hours to obtain ZT-1. The pore volume, specific surface area, and divisible pore diameter of ZT-1 were measured by N2 adsorption method and are shown in Table 1.
[0115] (5) Take 1000 g of support ZT1 and impregnate it with 800 mL of a mixed aqueous solution composed of molybdenum trioxide, basic nickel carbonate, phosphoric acid, and citric acid (the mixed aqueous solution contains 248 g / L MoO3, 55 g / L NiO, 51 g / L P2O5, and 40 g / L citric acid) for 1 hour. Dry it at 120 °C for 3 hours and calcine it at 400 °C under a nitrogen atmosphere for 3 hours to obtain hydrogenation catalyst C1. Based on the total weight of the catalyst, the content of molybdenum oxide and nickel oxide in catalyst C1 was determined by X-ray fluorescence spectrometry (the specific method is described in Petrochemical Analytical Methods RIPP133-90). The determination results are shown in Table 2.
[0116] Example 2
[0117] The reaction raw materials were prepared according to the method and conditions of Example 1, wherein:
[0118] 4L of aluminum sulfate solution, with a concentration of 50.0g / L based on aluminum oxide;
[0119] 6.5L sodium aluminate solution, with an Al2O3 concentration of 220g / L and a Na2O concentration of 227g / L.
[0120] 2L of Na2CO3 solution, concentration 200g / L.
[0121] The preparation of pseudoboehmite according to the method provided by this invention includes the following specific steps:
[0122] (1) Add the prepared 4L aluminum sulfate solution and 1.2L sodium aluminate solution to two raw material tanks respectively. Use a metering pump to adjust and control the flow rate volume ratio of aluminum sulfate solution to sodium aluminate solution to 3.62. Add them in parallel to a 2.0L neutralization reactor for continuous neutralization reaction at a temperature of 55℃, pH of 9.2 and residence time of 20min. The slurry overflows into the aging reactor.
[0123] (2) Add 350 mL of Na2CO3 solution to the neutralized slurry (neutralized slurry), adjust the pH to 10.5, and heat to 85℃ and hold at that temperature for 9 h for the first aging. Filter the slurry after the first aging (first aged slurry) using a vacuum filter, and wash with 60 L of deionized water at 90℃ to obtain a filter cake (i.e., the first aged solid product) with a Na2O content of 0.2%.
[0124] (3) The filter cake was slurried with deionized water to form 5.5L of slurry containing the first aging solid product, with a slurry concentration of 55g / L based on alumina. 5mL of Na2CO3 solution was added to the slurry containing the first aging solid product to adjust the pH of the slurry to 9.0. The slurry was heated to 80℃ and kept at that temperature for 4h for the second aging. The filter cake (the second aging solid product) was dried (drying temperature was 150℃) to form pseudoboehmite PB-2.
[0125] XRD characterization revealed that PB-2 possesses a pseudoboehmite structure. The relative crystallinity and grain size of the pseudoboehmite were calculated based on the 2θ = 38° peak in the pseudoboehmite phase diagram, and the results are shown in Table 1. PB-2 was then calcined in a crucible at 600℃ for 3 hours to obtain alumina powder A-2. A-2 exhibits a γ-alumina phase, and its chemical composition was characterized by XRF, with the results listed in Table 1. The pore volume, specific surface area, and dilatant pore diameter of A-2 were measured using the N2 adsorption method, and the results are shown in Table 1.
[0126] (4) Take 100g of PB-2, add 85g of deionized water, 3.2mL of concentrated nitric acid, and 3.0g of guar gum powder. Mix thoroughly and knead evenly on an extruder to obtain a paste. Extrude the paste into shape on the extruder and dry it in an oven at 120℃ for 4 hours. The dried strips are then calcined at 600℃ in a tubular calcining furnace for 3 hours to obtain ZT-2. The pore volume, specific surface area, and dilatant pore diameter of ZT-2 were measured by N2 adsorption method and are shown in Table 1.
[0127] (5) Take 1000 g of support ZT2 and impregnate it with 800 mL of a mixed aqueous solution composed of molybdenum trioxide, basic nickel carbonate, phosphoric acid, and citric acid (the mixed aqueous solution contains 250 g / L MoO3, 64 g / L NiO, 52 g / L P2O5, and 50 g / L citric acid) for 1 hour. Dry it at 120 °C for 3 hours and calcine it at 450 °C under a nitrogen atmosphere for 3 hours to obtain hydrogenation catalyst C2. Based on the total weight of the catalyst, the content of molybdenum oxide and nickel oxide in catalyst C2 was determined by X-ray fluorescence spectrometry (the specific method is described in Petrochemical Analytical Methods RIPP133-90). The determination results are shown in Table 2.
[0128] Example 3
[0129] The reaction raw materials were prepared according to the method and conditions of Example 1, wherein:
[0130] 4L of aluminum sulfate solution, with a concentration of 50.0g / L based on aluminum oxide;
[0131] 6.5L sodium aluminate solution, with an Al2O3 concentration of 220g / L and a Na2O concentration of 227g / L.
[0132] 2L of Na2CO3 solution, concentration 200g / L.
[0133] The preparation of pseudoboehmite according to the method provided by this invention includes the following specific steps:
[0134] (1) Add 4L of aluminum sulfate solution and 1.2L of sodium aluminate solution to two raw material tanks respectively. Use a metering pump to adjust and control the flow rate volume ratio of aluminum sulfate solution to sodium aluminate solution to 3.63. Add them in parallel to a 2.0L neutralization reactor for neutralization reaction. The temperature is 65℃, the pH is 8.7, and the residence time is 20min. The slurry overflows into the aging reactor.
[0135] (2) Add 750 mL of Na2CO3 solution to the neutralized slurry (neutralized slurry), adjust the pH to 10.3, and heat to 82℃ and hold at that temperature for 25 h for the first aging. Filter the slurry after the first aging (first aged slurry) using a vacuum filter, and wash with 60 L of deionized water at 90℃ to obtain a filter cake (i.e., the first aged solid product) with a Na2O content of 0.38%.
[0136] (3) The filter cake was slurried with deionized water to form 5L of slurry containing the first aging solid product, with a slurry concentration of 60g / L based on alumina. The slurry containing the first aging solid product was heated to 88℃ for 3h at a pH of 9.4 for the second aging. The filter cake (the second aging solid product) was dried (drying temperature was 130℃) to obtain boehmite PB-3.
[0137] XRD characterization revealed that PB-3 possesses a pseudoboehmite structure. The relative crystallinity and grain size of the pseudoboehmite were calculated based on the 2θ = 38° peak in the pseudoboehmite phase diagram, and the results are shown in Table 1. PB-3 was calcined in a crucible at 600℃ for 3 hours to obtain alumina powder A-3. A-3 exhibits a γ-alumina phase. The chemical composition of A-3 was characterized by XRF, and the results are listed in Table 1. The pore volume, specific surface area, and dilatant pore diameter of A-3 were measured using the N2 adsorption method, and the results are shown in Table 1.
[0138] (4) Take 100g of PB-3, add 82g of deionized water, 5.0mL of 36% acetic acid, and 3.0g of guar gum powder. Mix thoroughly and knead evenly on an extruder to obtain a paste. Extrude the paste into shape on the extruder and dry it in an oven at 120℃ for 4 hours. The dried strips are then calcined at 600℃ for 3 hours in a tubular calcining furnace to obtain ZT-3. The pore volume, specific surface area, and dilatant pore diameter of ZT-3 were measured by N2 adsorption method and are shown in Table 1.
[0139] (5) The ZT3 support was impregnated with 800 mL of a mixed aqueous solution consisting of molybdenum trioxide, basic nickel carbonate, and phosphoric acid (containing 328 g / L MoO3, 71 g / L NiO, 66 g / L P2O5, and 20 g / L ethylene glycol) for 1 hour, dried at 120°C for 3 hours, and calcined at 400°C under a nitrogen atmosphere for 3 hours to obtain the hydrogenation catalyst C3. The content of molybdenum oxide and nickel oxide in catalyst C3 was determined by X-ray fluorescence spectrometry based on the total weight of the catalyst (specific method is described in Petrochemical Analytical Methods RIPP133-90). The results are shown in Table 2.
[0140] Example 4
[0141] The reaction raw materials were prepared according to the method and conditions of Example 1, wherein:
[0142] 4L of aluminum sulfate solution, with a concentration of 50.0g / L based on aluminum oxide;
[0143] 6.5L sodium aluminate solution, with an Al2O3 concentration of 220g / L and a Na2O concentration of 227g / L.
[0144] 2L of Na2CO3 solution, concentration 200g / L.
[0145] The preparation of pseudoboehmite according to the method provided by this invention includes the following specific steps:
[0146] (1) Add 4L of aluminum sulfate solution and 1.2L of sodium aluminate solution to two raw material tanks respectively. Use a metering pump to adjust and control the flow rate volume ratio of aluminum sulfate solution to sodium aluminate solution to 3.72. Add them in parallel to a 2.0L neutralization reactor for neutralization reaction at a temperature of 45℃, pH of 9.5 and residence time of 20min. The slurry overflows into the aging reactor.
[0147] (2) Add 10 mL of Na2CO3 solution to the slurry after neutralization (neutralized slurry), adjust the pH to 9.6, and heat to 95℃ and hold at that temperature for 4 hours for the first aging. Filter the slurry after the first aging (first aged slurry) using a vacuum filter, and wash with 60 L of deionized water at 90℃ to obtain a filter cake (i.e., the first aged solid product) with a Na2O content of 0.15%.
[0148] (3) The filter cake was slurried with deionized water to form 6L of slurry containing the first aging solid product. The concentration of the slurry, calculated as alumina, was 45g / L. The pH of the slurry containing the first aging solid product was 8.8. The slurry was heated to 70℃ and kept at that temperature for 5h for the second aging. The filter cake (the second aging solid product) was dried (drying temperature was 140℃) to obtain boehmite PB-4.
[0149] XRD characterization revealed that PB-4 possesses a pseudoboehmite structure. The relative crystallinity and grain size of the pseudoboehmite were calculated based on the 2θ = 38° peak in the pseudoboehmite phase diagram, and the results are shown in Table 1. PB-4 was calcined in a crucible at 600℃ for 3 hours to obtain alumina powder A-4. A-4 exhibits a γ-alumina phase. The chemical composition of A-4 was characterized by XRF, and the results are listed in Table 1. The pore volume, specific surface area, and dilatant pore diameter of A-4 were measured using the N2 adsorption method, and the results are shown in Table 1.
[0150] (4) Take 100g of PB-4, add 82g of deionized water, 5.0mL of 36% acetic acid, and 3.0g of guar gum powder. Mix thoroughly and knead evenly on an extruder to obtain a paste. Extrude the paste into shape on the extruder and dry it in an oven at 120℃ for 4 hours. The dried strips are then calcined at 600℃ for 3 hours in a tubular calcining furnace to obtain ZT-4. The pore volume, specific surface area, and dilatant pore diameter of ZT-4 were measured by N2 adsorption method and are shown in Table 1.
[0151] (5) The ZT4 support was impregnated with 800 mL of a mixed aqueous solution consisting of molybdenum trioxide, basic cobalt carbonate, phosphoric acid, and glycerol (containing 288 g / L MoO3, 61 g / L CoO, 35 g / L P2O5, and 10 g / L glycerol) for 2 hours, dried at 120°C for 3 hours, and calcined at 460°C under a nitrogen atmosphere for 3 hours to obtain the hydrogenation catalyst C4. The content of molybdenum oxide and nickel oxide in catalyst C4 was determined by X-ray fluorescence spectrometry based on the total weight of the catalyst (specific method is described in Petrochemical Analytical Methods RIPP133-90). The results are shown in Table 2.
[0152] Example 5
[0153] The reaction raw materials were prepared according to the method and conditions of Example 1, wherein:
[0154] A 5L aluminum sulfate solution has a concentration of 40.0g / L based on aluminum oxide.
[0155] 6.5L sodium aluminate solution, with an Al2O3 concentration of 220g / L and a Na2O concentration of 227g / L.
[0156] 2L of Na2CO3 solution, concentration 200g / L.
[0157] The preparation of pseudoboehmite according to the method provided by this invention includes the following specific steps:
[0158] (1) Add the prepared 5L aluminum sulfate solution and 1.2L sodium aluminate solution to two raw material tanks respectively. Use a metering pump to adjust and control the flow rate volume ratio of aluminum sulfate solution to sodium aluminate solution to 3.90. Add them in parallel to a 2.0L neutralization reactor for continuous neutralization reaction at a temperature of 55℃, pH of 8.0 and residence time of 20min. The slurry overflows into the aging reactor.
[0159] (2) Add 1250 mL of Na2CO3 solution to the neutralized slurry (neutralized slurry), adjust the pH to 10.2, and heat to 85℃ and hold at that temperature for 9 hours for the first aging. Filter the slurry after the first aging (first aged slurry) using a vacuum filter, and wash with 60 L of deionized water at 90℃ to obtain a filter cake (i.e., the first aged solid product) with a Na2O content of 0.15%.
[0160] (3) The filter cake was slurried with deionized water to form 5.5L of slurry containing the first aging solid product, with a slurry concentration of 55g / L based on alumina. 5mL of Na2CO3 solution was added to the slurry containing the first aging solid product to adjust the pH of the slurry to 9.0. The slurry was heated to 80℃ and kept at that temperature for 4h for the second aging. The filter cake (the second aging solid product) was dried (drying temperature was 150℃) to form pseudoboehmite PB-5.
[0161] XRD characterization revealed that PB-5 possesses a pseudoboehmite structure. The relative crystallinity and grain size of the pseudoboehmite were calculated based on the 2θ = 38° peak in the pseudoboehmite phase diagram, and the results are shown in Table 1. PB-5 was then calcined in a crucible at 600℃ for 3 hours to obtain alumina powder A-5. A-5 exhibits a γ-alumina phase, and its chemical composition was characterized by XRF, with the results listed in Table 1. The pore volume, specific surface area, and dilatant pore diameter of A-5 were measured using the N2 adsorption method, and the results are shown in Table 1.
[0162] The catalyst was prepared according to the method in Example 2.
[0163] Example 6
[0164] The reaction raw materials were prepared according to the method and conditions of Example 1, wherein:
[0165] 4L of aluminum sulfate solution, with a concentration of 50.0g / L based on aluminum oxide;
[0166] 6.5L sodium aluminate solution, with an Al2O3 concentration of 220g / L and a Na2O concentration of 227g / L.
[0167] 2L of Na2CO3 solution, concentration 200g / L.
[0168] The preparation of pseudoboehmite according to the method provided by this invention includes the following specific steps:
[0169] (1) Add 4L of aluminum sulfate solution and 1.2L of sodium aluminate solution to two raw material tanks respectively. Use a metering pump to adjust and control the flow rate volume ratio of aluminum sulfate solution to sodium aluminate solution to 3.63. Add them in parallel to a 2.0L neutralization reactor for neutralization reaction. The temperature is 65℃, the pH is 8.7, and the residence time is 20min. The slurry overflows into the aging reactor.
[0170] (2) Add 66 mL of Na2CO3 solution to the slurry after neutralization (neutralized slurry), adjust the pH to 9.1, and heat to 82℃ and hold at that temperature for 25 h for the first aging. Filter the slurry after the first aging (first aged slurry) using a vacuum filter, and wash with 60 L of deionized water at 90℃ to obtain a filter cake (i.e., the first aged solid product) with a Na2O content of 0.21%.
[0171] (3) The filter cake was slurried with deionized water to form 5L of slurry containing the first aging solid product, with a slurry concentration of 60g / L based on alumina. The slurry containing the first aging solid product was heated to 88℃ and kept at that temperature for 3h for the second aging. The filter cake (the second aging solid product) was dried (drying temperature was 130℃) to obtain boehmite PB-6.
[0172] XRD characterization revealed that PB-6 possesses a pseudoboehmite structure. The relative crystallinity and grain size of the pseudoboehmite were calculated based on the 2θ = 38° peak in the pseudoboehmite phase diagram, and the results are shown in Table 1. PB-6 was calcined in a crucible at 600℃ for 3 hours to obtain alumina powder A-6. A-6 exhibits a γ-alumina phase. The chemical composition of A-6 was characterized by XRF, and the results are listed in Table 1. The pore volume, specific surface area, and dilatant pore diameter of A-6 were measured using the N2 adsorption method, and the results are shown in Table 1.
[0173] The catalyst was prepared according to the method in Example 3.
[0174] Example 7
[0175] The reaction raw materials were prepared according to the method and conditions of Example 1, wherein:
[0176] 4L of aluminum sulfate solution, with a concentration of 50.0g / L based on aluminum oxide;
[0177] 6.5L sodium aluminate solution, with an Al2O3 concentration of 220g / L and a Na2O concentration of 227g / L.
[0178] 2L of Na2CO3 solution, concentration 200g / L.
[0179] The preparation of pseudoboehmite according to the method provided by this invention includes the following specific steps:
[0180] (1) Add 4L of aluminum sulfate solution and 1.2L of sodium aluminate solution to two raw material tanks respectively. Use a metering pump to adjust and control the flow rate volume ratio of aluminum sulfate solution to sodium aluminate solution to 3.72. Add them in parallel to a 2.0L neutralization reactor for neutralization reaction at a temperature of 45℃, pH of 9.5 and residence time of 20min. The slurry overflows into the aging reactor.
[0181] (2) Add 10 mL of Na2CO3 solution to the slurry after neutralization (neutralized slurry), adjust the pH to 9.6, and heat to 95℃ and hold at that temperature for 4 hours for the first aging. Filter the slurry after the first aging (first aged slurry) using a vacuum filter, and wash with 70 L of deionized water at 90℃ to obtain a filter cake (i.e., the first aged solid product) with a Na2O content of 0.12%.
[0182] (3) The filter cake was slurried with deionized water to form 4.0L of slurry containing the first aging solid product, with a slurry concentration of 75g / L based on alumina. The pH of the slurry containing the first aging solid product was 8.5. The slurry was heated to 70℃ and kept at that temperature for 5h for the second aging. The filter cake (the second aging solid product) was dried (drying temperature was 140℃) to obtain boehmite PB-7.
[0183] XRD characterization revealed that PB-7 possesses a pseudoboehmite structure. The relative crystallinity and grain size of the pseudoboehmite were calculated based on the 2θ = 38° peak in the pseudoboehmite phase diagram, and the results are shown in Table 1. PB-7 was calcined in a crucible at 600℃ for 3 hours to obtain alumina powder A-7. A-7 exhibits a γ-alumina phase. The chemical composition of A-7 was characterized by XRF, and the results are listed in Table 1. The pore volume, specific surface area, and dilatant pore diameter of A-7 were measured using the N2 adsorption method, and the results are shown in Table 1.
[0184] The catalyst was prepared according to the method in Example 4.
[0185] Example 8
[0186] 1000g of the ZT4 support from Example 4 was impregnated with 800mL of a mixed aqueous solution consisting of molybdenum trioxide, basic nickel carbonate, phosphoric acid, and glucose (containing 231g / L MoO3, 28g / L NiO, 38g / L P2O5, and 98g / L glucose) for 2 hours. The impregnation was then followed by drying at 120°C for 3 hours and calcination at 420°C under a nitrogen atmosphere for 3 hours to obtain the hydrogenation catalyst C8. Based on the total weight of the catalyst, the contents of molybdenum oxide and nickel oxide in catalyst C8 were determined by X-ray fluorescence spectrometry (specific method is described in Petrochemical Analytical Methods RIPP 133-90). The results are shown in Table 2.
[0187] Example 9
[0188] Take 1000g of the support ZT4 from Example 4 and prepare a catalyst according to the method in Example 4, except that the concentration of glycerol is 80g / L.
[0189] Comparative Example 1
[0190] The reaction raw materials were prepared according to the method and conditions of Example 1, wherein:
[0191] 4L of aluminum sulfate solution, with a concentration of 50.0g / L based on aluminum oxide;
[0192] 6.5L sodium aluminate solution, with an Al2O3 concentration of 220g / L and a Na2O concentration of 227g / L.
[0193] 2L of Na2CO3 solution, concentration 200g / L.
[0194] The preparation of pseudoboehmite according to the method provided by this invention includes the following specific steps:
[0195] (1) Add 4L of aluminum sulfate solution and 1.2L of sodium aluminate solution to two raw material tanks respectively. Use a metering pump to adjust and control the flow rate volume ratio of aluminum sulfate solution to sodium aluminate solution to 4.20. Add them in parallel to a 2.0L neutralization reactor for neutralization reaction at a temperature of 60℃, pH of 6.3 and residence time of 20min. The slurry overflows into the aging reactor.
[0196] (2) Add 1700 mL of Na2CO3 solution to the neutralized slurry (neutralized slurry), adjust the pH to 10.2, and heat to 85℃ for 3 hours for the first aging. Filter the slurry after the first aging (first aged slurry) using a vacuum filter, and wash with 60 L of deionized water at 90℃ to obtain a filter cake (i.e., the first aged solid product) with a Na2O content of 0.4%.
[0197] (3) The filter cake was slurried with deionized water to form 6L of slurry containing the first aging solid product. The concentration of the slurry was 45g / L based on alumina. 20mL of Na2CO3 solution was added to the slurry containing the first aging solid product to adjust the pH of the slurry to 9.5. The slurry was heated to 62℃ and kept at that temperature for 2h for the second aging. The filter cake (the second aging solid product) was dried (drying temperature was 120℃) to obtain pseudoboehmite CPB-1.
[0198] XRD characterization revealed that CPB-1 possesses a pseudoboehmite structure. The relative crystallinity and grain size of the pseudoboehmite were calculated based on the 2θ = 38° peak in the pseudoboehmite phase diagram, and the results are shown in Table 1. CPB-1 was calcined in a crucible at 600℃ for 3 hours to obtain alumina powder CA-1. CA-1 exhibits a γ-alumina phase. The chemical composition of CA-1 was characterized by XRF, and the results are listed in Table 1. The pore volume, specific surface area, and dilatant pore diameter of CA-1 were measured using the N2 adsorption method, and the results are shown in Table 1.
[0199] The catalyst was prepared according to the method in Example 1.
[0200] Comparative Example 2
[0201] The reaction raw materials were prepared according to the method and conditions of Example 1, wherein:
[0202] 4L of aluminum sulfate solution, with a concentration of 50.0g / L based on aluminum oxide;
[0203] 6.5L sodium aluminate solution, with an Al2O3 concentration of 220g / L and a Na2O concentration of 227g / L.
[0204] 2L of Na2CO3 solution, concentration 200g / L.
[0205] The preparation of pseudoboehmite according to the method provided by this invention includes the following specific steps:
[0206] (1) Add 4L of aluminum sulfate solution and 1.2L of sodium aluminate solution to two raw material tanks respectively. Use a metering pump to adjust and control the flow rate volume ratio of aluminum sulfate solution to sodium aluminate solution to 4.05. Add them in parallel to a 2.0L neutralization reactor for neutralization reaction at a temperature of 45℃, pH of 7.0 and residence time of 20min. The slurry overflows into the aging reactor.
[0207] (2) Add 420 mL of Na2CO3 solution to the neutralized slurry (neutralized slurry), adjust the pH to 8.7, and heat to 95℃ and hold at that temperature for 4 hours for the first aging. Filter the slurry after the first aging (first aged slurry) using a vacuum filter, and wash with 60 L of deionized water at 90℃ to obtain a filter cake (i.e., the first aged solid product) with a Na2O content of 0.2%.
[0208] (3) The filter cake was slurried with deionized water to form 6L of slurry containing the first aging solid product. The concentration of the slurry was 45g / L based on alumina. 32mL of Na2CO3 solution was added to the slurry containing the first aging solid product to adjust the pH of the slurry to 9.5. The slurry was heated to 62℃ and kept at that temperature for 2h for the second aging. The filter cake (the second aging solid product) was dried (drying temperature was 120℃) to obtain pseudoboehmite CPB-2.
[0209] XRD characterization revealed that CPB-2 possesses a pseudoboehmite structure. The relative crystallinity and grain size of the pseudoboehmite were calculated based on the 2θ = 38° peak in the pseudoboehmite phase diagram, and the results are shown in Table 1. CPB-2 was calcined in a crucible at 600℃ for 3 hours to obtain alumina powder CA-2. CA-2 exhibits a γ-alumina phase. The chemical composition of CA-2 was characterized by XRF, and the results are listed in Table 1. The pore volume, specific surface area, and dilatant pore diameter of CA-2 were measured using the N2 adsorption method, and the results are shown in Table 1.
[0210] The catalyst was prepared according to the method in Example 2.
[0211] Comparative Example 3
[0212] Preparation of reaction raw materials:
[0213] The reaction raw materials were prepared according to the method and conditions of Example 1, wherein:
[0214] 4L of aluminum sulfate solution, with a concentration of 50.0g / L based on aluminum oxide;
[0215] 6.5L sodium aluminate solution, with an Al2O3 concentration of 220g / L and a Na2O concentration of 227g / L.
[0216] 2L of Na2CO3 solution, concentration 200g / L.
[0217] The preparation of pseudoboehmite according to the method provided by this invention includes the following specific steps:
[0218] (1) Add 4L of aluminum sulfate solution and 1.2L of sodium aluminate solution to two raw material tanks respectively. Use a metering pump to adjust and control the flow rate volume ratio of aluminum sulfate solution to sodium aluminate solution to 3.63. Add them in parallel to a 2.0L neutralization reactor for neutralization reaction. The temperature is 65℃, the pH is 8.7, and the residence time is 20min. The slurry overflows into the aging reactor.
[0219] (2) The slurry after neutralization (neutralized slurry) was heated directly to 82℃ for 25 hours without adjusting the pH with Na2CO3 solution, and then subjected to the first aging process. The slurry after the first aging process was filtered using a vacuum filter and washed with 60L of deionized water at 90℃. The Na2O content in the filter cake (the first aging solid product) was 0.18%.
[0220] (3) The filter cake was slurried with deionized water to form 5L of slurry containing the first aging solid product, with a slurry concentration of 60g / L based on alumina. The slurry containing the first aging solid product was heated to 88℃ and kept at that temperature for 3h for a second aging. The filter cake (the second aging solid product) was dried (drying temperature was 130℃) to obtain pseudoboehmite CPB-3.
[0221] XRD characterization revealed that CPB-3 possesses a pseudoboehmite structure. The relative crystallinity and grain size of the pseudoboehmite were calculated based on the 2θ = 38° peak in the pseudoboehmite phase diagram, and the results are shown in Table 1. CPB-3 was calcined in a crucible at 600℃ for 3 hours to obtain alumina powder CA-3. CA-3 exhibits a γ-alumina phase. The chemical composition of CA-3 was characterized by XRF, and the results are listed in Table 1. The pore volume, specific surface area, and dilatant pore diameter of CA-3 were measured using the N2 adsorption method, and the results are shown in Table 1.
[0222] The catalyst was prepared according to the method in Example 1.
[0223] Comparative Example 4
[0224] The method is the same as in Example 1, except that the filter cake after filtration and washing of the slurry after the first aging (first aging slurry) is not subjected to step (3) slurrying and second aging. The filter cake after the first aging is dried (drying temperature is 120°C) to obtain pseudoboehmite CPB-4.
[0225] XRD characterization revealed that CPB-4 possesses a pseudoboehmite structure. The relative crystallinity and grain size of the pseudoboehmite were calculated based on the 2θ = 38° peak in the pseudoboehmite phase diagram, and the results are shown in Table 1. CPB-4 was calcined in a crucible at 600℃ for 3 hours to obtain alumina powder CA-4. CA-4 exhibits a γ-alumina phase. The chemical composition of CA-4 was characterized by XRF, and the results are listed in Table 1. The pore volume, specific surface area, and dilatant pore diameter of CA-4 were measured using the N2 adsorption method, and the results are shown in Table 1.
[0226] The catalyst was prepared according to the method in Example 1.
[0227] Comparative Example 5
[0228] The method was followed as in Example 1, except that the first aging temperature was 60°C. Washing and drying yielded pseudoboehmite CPB-5.
[0229] XRD characterization revealed that CPB-5 possesses a pseudoboehmite structure. The relative crystallinity and grain size of the pseudoboehmite were calculated based on the 2θ = 38° peak in the pseudoboehmite phase diagram, and the results are shown in Table 1. CPB-5 was calcined in a crucible at 600℃ for 3 hours to obtain alumina powder CA-5. CA-5 exhibits a γ-alumina phase. The chemical composition of CA-5 was characterized by XRF, and the results are listed in Table 1. The pore volume, specific surface area, and dilatant pore diameter of CA-5 were measured using the N2 adsorption method, and the results are shown in Table 1.
[0230] The catalyst was prepared according to the method in Example 1.
[0231] Comparative Example 6
[0232] The method is the same as in Example 4, except that the slurry after the first aging (first aging slurry) is filtered and washed to obtain a filter cake, which is then slurried with deionized water to form a slurry containing the first aging solid product. 45 mL of Na2CO3 solution is added to the slurry containing the first aging solid product to adjust the pH to 10.2, and then the mixture is heated to 70°C and held at that temperature for 5 hours for a second aging process. The resulting filter cake (second aging solid product) is then dried (at a drying temperature of 140°C) to obtain boehmite CPB-6.
[0233] XRD characterization revealed that CPB-6 possesses a pseudoboehmite structure. The relative crystallinity and grain size of the pseudoboehmite were calculated based on the 2θ = 38° peak in the pseudoboehmite phase diagram, and the results are shown in Table 1. CPB-4 was calcined in a crucible at 600℃ for 3 hours to obtain alumina powder CA-6. CA-6 exhibits a γ-alumina phase. The chemical composition of CA-6 was characterized by XRF, and the results are listed in Table 1. The pore volume, specific surface area, and dilatant pore diameter of CA-6 were measured using the N2 adsorption method, and the results are shown in Table 1.
[0234] The catalyst was prepared according to the method in Example 1.
[0235] Comparative Example 7
[0236] CTZ7 is a carrier industrially produced by Changling Catalyst Branch. The dry adhesive powder used is a commonly used mesoporous dry adhesive powder (pore volume of 0.9 ml / g, specific surface area of 280 m²). 2 The pore volume, specific surface area, and pore diameter of CZT-7 were measured using the N2 adsorption method ( / g), as shown in Table 1.
[0237] 1000 grams of support CTZ-7 were used to prepare catalyst DC7 using the method described in Example 1.
[0238] Table 1
[0239]
[0240]
[0241] Table 2
[0242]
[0243]
[0244] Test case
[0245] The test examples are used to illustrate the hydrogenation activity and reaction stability of the hydrogenation catalyst of the present invention.
[0246] The hydrogenation catalysts prepared in the above-mentioned 100 mL examples and comparative examples were crushed into particles with a diameter of 2-3 mm and then pre-sulfurized. The pre-sulfurization conditions included: using Jingmen Changyi kerosene containing 5 wt% dimethyl disulfide as the sulfiding oil, and a liquid hourly space velocity (LHSV) of 1.2 h⁻¹ for the sulfiding oil. -1The hydrogen partial pressure was 14.0 MPa, the hydrogen-to-oil volume ratio was 400, and the reaction was carried out at a constant temperature of 360 °C for 3 hours. Evaluation was then conducted in a 100 mL small fixed-bed reactor (catalyst loading: 100 mL). The feedstock was Kuwaiti atmospheric residue oil (sulfur content: 3.5 wt%, nitrogen content: 0.21 wt%, carbon residue: 11.7 wt%, nickel content: 11.7 μg / g, vanadium content: 31.7 μg / g), and the reaction was carried out at a reaction temperature of 380 °C, a hydrogen partial pressure of 14 MPa, and a liquid hourly space velocity (LHSV): 0.6 h⁻¹. -1 The hydrogenation activity was measured when the hydrogen-to-oil volume ratio was 600 and the operating time was 200 h.
[0247] The sulfur content in the oil sample was determined using the coulombic method (see Petrochemical Analytical Methods RIPP 62-90 for details). The carbon residue content in the oil sample was determined using the micro-method (see Petrochemical Analytical Methods RIPP 149-90 for details).
[0248] Table 3
[0249]
[0250]
[0251] As can be seen from Table 3, the hydrogenation catalyst provided by the present invention has better and lower product sulfur content and carbon residue under the same conditions, and the hydrogenation catalyst provided by the present invention has higher propylene yield under the same conditions.
[0252] The preferred embodiments of the present invention have been described in detail above; however, the present invention is not limited thereto. Within the scope of the inventive concept, various simple modifications can be made to the technical solutions of the present invention, including combinations of various technical features in any other suitable manner. These simple modifications and combinations should also be considered as the content disclosed in the present invention and are all within the protection scope of the present invention.
Claims
1. A hydrogenation catalyst, wherein, The catalyst comprises an alumina support, a hydrogenation active metal component, and carbon. The hydrogenation active metal component includes Group VIII and Group VIB metals. The pore concentration A of the alumina support is 0.8-3, and the pore volume of the 4-13 nm pores in the alumina support accounts for 78-95% of the total pore volume. Based on the total weight of the catalyst, the carbon content is 0.1-5%.
2. The hydrogenation catalyst according to claim 1, wherein, The pore concentration A of the alumina carrier is 1.9-2.5; And / or, the pore volume of the 4-13 nm pores in the alumina carrier accounts for 85-90% of the total pore volume; And / or, based on the total weight of the catalyst, the carbon content is 0.3-2%.
3. The hydrogenation catalyst according to claim 1 or 2, wherein, The pore volume of the alumina support is 0.58-0.75 mL / g; Preferably, the specific surface area of the alumina carrier is 250-310 m². 2 / g; Preferably, the alumina carrier has a pore diameter of 5-9 nm; Preferably, based on the dry weight of the alumina carrier and in terms of oxides, the sodium content is 0.01-0.05%, more preferably 0.012-0.03%, and the S content is 0.1-1%, more preferably 0.2-0.8%.
4. The hydrogenation catalyst according to claim 1 or 2, wherein, Based on the total weight of the catalyst, the content of the alumina support is 30-99%, the content of the Group VIII metal element (calculated as oxide) is 0.5-20%, and the content of the Group VIB metal element (calculated as oxide) is 0.5-50%. Preferably, based on the total weight of the catalyst, the content of the alumina support is 40-94%, the content of the Group VIII metal element (calculated as oxide) is 1-15%, and the content of the Group VIB metal element (calculated as oxide) is 5-45%. Preferably, the Group VIII metallic element is cobalt and / or nickel; Preferably, the Group VIB metal element is molybdenum and / or tungsten; Preferably, the TEM active phase length of the catalyst is 1.8-5 nm, and more preferably 2.1-3.2 nm.
5. A method for preparing a hydrogenation catalyst, wherein, The method includes the following steps: (1) Neutralize aluminum sulfate solution with alkaline solution to obtain neutralized slurry. The pH of the neutralization reaction is 8-10. (2) The neutralized slurry is subjected to a first aging process to obtain a first aged solid product. The pH of the first aging process is higher than that of the neutralization reaction. (3) In the presence of a solvent, the first aged solid product is subjected to a second aging to obtain a second aged solid product. Then, the second aged solid product is subjected to a first drying to obtain boehmite. The pH of the first aging is higher than that of the second aging. (4) The pseudoboehmite is optionally shaped, and then subjected to a second drying and a first calcination to obtain an alumina carrier; (5) A carbon source and a hydrogenation active metal component are introduced into the alumina support, followed by a third drying and a second calcination. The second calcination is carried out under nitrogen and / or an inert atmosphere. The hydrogenation active metal component includes Group VIII metal elements and Group VIB metal elements. The amount of carbon source is such that the carbon content in the prepared catalyst is 0.1-5% based on the total weight of the catalyst.
6. The method according to claim 5, wherein, The pH of the first aging process is 0.05-2.2 higher than the pH of the neutralization reaction, preferably 0.1-2 higher; Preferably, the pH of the first aging is 0.5-1.8 higher than the pH of the second aging, and more preferably 0.7-1.5 higher.
7. The method according to claim 5 or 6, wherein, In step (1), the concentration of the aluminum sulfate solution, calculated as aluminum oxide, is 40-100 g / L, preferably 50-90 g / L; And / or, in step (1), the alkaline solution is selected from at least one of sodium hydroxide solution, sodium carbonate solution and sodium aluminate solution, preferably sodium aluminate solution; Preferably, the volume ratio of the sulfuric acid solution to the alkaline solution is 3-4:1, more preferably 3.6-3.9:
1.
8. The method according to claim 5 or 6, wherein, In step (1), the neutralization reaction is carried out continuously or intermittently, preferably continuously; And / or, in step (1), the conditions for the neutralization reaction include: a temperature of 45-75°C and a residence time of 5-30 min; Preferably, in step (1), the pH of the neutralization reaction is 8.2-9.
5.
9. The method according to claim 5 or 6, wherein, In step (2), the conditions for the first aging include: a temperature of 75-99℃ and a time of 2-30h; Preferably, in step (2), the conditions for the first aging include: a temperature of 81-98°C and a time of 4-26 hours; Preferably, in step (2), the pH of the first aging is 9-10.8, more preferably 9.5-10.6; Preferably, step (2) further includes: optionally adding an aluminum-free alkaline compound solution to the neutralized slurry to adjust the pH to 9-10.8, preferably to 9.5-10.6, for a first aging.
10. The method according to claim 5 or 6, wherein, Step (3) further includes: mixing the first aged solid product and a solvent to form a slurry, thereby obtaining a slurry containing the first aged solid product; Preferably, in step (3), the concentration of the slurry containing the first aged solid product, based on alumina, is 40-150 g / L, more preferably 45-70 g / L; Preferably, in step (3), the conditions for the second aging include: a temperature of 55-90°C and a time of 2-6 hours; Preferably, in step (3), the conditions for the second aging include: a temperature of 60-88°C and a time of 3-5 hours; Preferably, in step (3), the pH of the second aging process is 8.5-10.5, and more preferably 8.7-9.
8.
11. The method according to claim 5 or 6, wherein, In step (4), the conditions for the first calcination include: a temperature of 450-800℃ and a time of 1-10h; Preferably, in step (4), the conditions for the first roasting include: a temperature of 500-700℃ and a time of 2-6h.
12. The method according to claim 5 or 6, wherein, In step (5), the conditions for the second calcination include: a temperature of 300-800℃ and a time of 1-10h; Preferably, in step (5), the conditions for the second calcination include: a temperature of 350-600℃ and a time of 2-6h.
13. The method according to claim 5 or 6, wherein, The amounts of Group VIII and Group VIB metals used in the prepared catalyst are such that, based on the total weight of the catalyst, the content of the alumina support is 30-99%, the content of the Group VIII metal as oxide is 0.5-20%, and the content of the Group VIB metal as oxide is 0.5-50%. Preferably, based on the total weight of the catalyst, the content of the alumina support is 40-94%, the content of the Group VIII metal element (calculated as oxide) is 1-15%, and the content of the Group VIB metal element (calculated as oxide) is 5-45%. Preferably, the Group VIII metallic element is cobalt and / or nickel; Preferably, the Group VIB metal element is molybdenum and / or tungsten.
14. The method according to claim 5 or 6, wherein, In step (5), the carbon source is selected from at least one of organic acids, organic alcohols, and carbohydrate compounds; Preferably, the organic acid is selected from at least one of acetic acid, maleic acid, oxalic acid, aminotriacetic acid, 1,2-cyclohexanediaminetetraacetic acid, citric acid, tartaric acid, and malic acid; Preferably, the organic alcohol is selected from at least one of glycerol, ethylene glycol, polyethylene glycol, diethylene glycol, butanediol, and propanol; Preferably, the carbohydrate compound is selected from at least one of glucose, maltose, lactose, and sucrose; Preferably, the amount of carbon source used is such that the carbon content in the prepared catalyst is 0.3-2% based on the total weight of the catalyst.
15. The use of the catalyst according to any one of claims 1-4 or the catalyst prepared by the method according to any one of claims 5-14 in the hydrotreating of hydrocarbon oils.